IMPLEMENTASI KURIKULUM 2013 PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMA NEGERI 4 TANJUNG JABUNG BARAT - Bambang Rismanto (LP3M Universitas Muhammadiyah Muara Bungo, 2021)
The objectives of this study is to understand the implementation of Curriculum 2013 in Subjects PAIBP in SMA Negeri 4 Tanjung Jabung Barat.This study is a qualitative research using interviews, observation, and documentation. Data analysis technique includes data reduction, data presentation, and conclusion/verification. The results showed that Curriculum 2013 has been implemented well by PAIBP teachers at the learning instruments development stage, the learning activity stage, and the learning evaluation stage. Learning instruments have been compiled in a comprehensive manner starting from indicators to lesson plan along with enrichment and remedial programs. PAIBP learning has implemented a student-centered scientific learning model. The evaluation has been carried out authentically even though the assessment of knowledge is dominant with an essay format.